Improvement of diaphragmatic performance through orthotopic application of decellularized extracellular matrix patch. (January 2016) - Piccoli, M.; Urbani, L.; Alvarez-Fallas, M.E.; Franzin, C.; Dedja, A.; Bertin, E.; Zuccolotto, G.; Rosato, A.; Pavan, P.; Elvassore, N.; De Coppi, P.; Pozzobon, M.
Abstract: Muscle tissue engineering can provide support to large congenital skeletal muscle defects using scaffolds able to allow cell migration, proliferation and differentiation. Acellular extracellular matrix (ECM) scaffold can generate a positive inflammatory response through the activation of anti-inflammatory T-cell populations and M2 polarized macrophages that together lead to a local pro-regenerative environment. This immunoregulatory effect is maintained when acellular matrices are transplanted in a xenogeneic setting, but it remains unclear whether it can be therapeutic in a model of muscle diseases. We demonstrated here for the first time that orthotopic transplantation of a decellularized diaphragmatic muscle from wild animals promoted tissue functional recovery in an established atrophic mouse model. In particular, ECM supported a local immunoresponse activating a pro-regenerative environment and stimulating host muscle progenitor cell activation and migration. These results indicate that acellular scaffolds may represent a suitable regenerative medicine option for improving performance of diseased muscles.